Is curcumin bioavailability a problem in humans: lessons from clinical trials. (2nd September 2019) - Kunnumakkara, Ajaikumar B.; Harsha, Choudhary; Banik, Kishore; Vikkurthi, Rajesh; Sailo, Bethsebie L.; Bordoloi, Devivasha; Gupta, Subash C.; Aggarwal, Bharat B.
ABSTRACT: Introduction : Since ancient times, turmeric has been used in several folklore remedies against various ailments. The principal component of turmeric is curcumin and its efficacy has been advocated in various in vitro, in vivo and clinical studies for different chronic diseases. However, some studies suggest that curcumin bioavailability is a major problem. Areas covered : This article discusses over 200 clinical studies with curcumin that have demonstrated the pronounced protective role of this compound against cardiovascular diseases, inflammatory diseases, metabolic diseases, neurological diseases, skin diseases, liver diseases, various types of cancer, etc. The review also describes the combination of curcumin with many natural and synthetic compounds as well as various formulations of curcumin that have shown efficacy in multiple clinical studies. Expert opinion : The therapeutic potential of curcumin, as demonstrated by clinical trials has overpowered the myth that poor bioavailability of curcumin poses a problem. Low curcumin bioavailability in certain studies has been addressed by using higher concentrations of curcumin within nontoxic limits. Moreover, curcumin, in combination with other compounds or as formulations, has shown enhanced bioavailability. Hence, bioavailability is not a problem in the curcumin-mediated treatment of chronic diseases. Therefore, this golden nutraceutical presents a safe, low-cost and effective treatment modality for different chronic diseases.